Eco‐innovations of firms: A longitudinal analysis of the roles of industry norms and proactive environmental strategy. (23rd September 2021) - Roxas, Banjo
Abstract: There is scant empirical longitudinal evidence in the extant eco‐innovation literature on how industry norms, standards and expectations influence firms' strategic choices and innovation activities in the context of environmental sustainability. This study fills this research gap by determining the causal effects of industry norms that promote environmentally sustainable business practices on developing a firm's proactive environmental strategy, which propels a firm's eco‐innovation outputs or those innovations considered environmentally sustainable. It utilises two waves of survey data involving 274 small and medium enterprises and the cross‐lagged panel method of longitudinal analysis to bring to light the explanatory mediating power of a firm's environmental strategy as a response to industry norms that push firms to pursue eco‐innovations. Drawing on institutional and strategic adaptation theories, this study's main findings on the causal and predictive temporal effects of industry norms on firm strategy and eco‐innovation offer robust empirical evidence that extends and overcomes the shortcomings of previous studies on firm‐level eco‐innovation and its institutional and strategy‐related determinants. This article presents the significant theoretical, empirical, methodological and practical implications of the study.